ERGONOMIC SITTING EDUCATION FOR THE PREVENTION OF TEXT NECK SYNDROME IN STUDENTS: EDUKASI DUDUK ERGONOMIS UNTUK PENCEGAHAN TEXT NECK SYNDROME PADA SISWA - Via Devi Surya Putri; Koyimah Nur Sholekhah; Sabrina Aprilia; Cherly Cantika Maharani; Faza Kamilatun Nuha; Andheta Maulidya; Arshy Prodyanatasari (WISDOM : Jurnal Pengabdian Kepada Masyarakat Wisdom, 2026)
Text Neck Syndrome is a musculoskeletal disorder related to excessive cell phone use. It is estimated that the prevalence of neck pain among 7-11-year-olds who spend 5-8 hours a day on cell phones is around 70%. This condition highlights the importance of proper education about the risks and prevention. This community service activity aims to provide students with knowledge about ergonomic sitting positions to prevent neck strain from excessive cell phone use at SD Modern Paramadina in Kediri City. This activity was carried out using a Participatory Action Research (PAR) approach with 17 students: 11 boys and 6 girls. The intervention provided was health education using PowerPoint media and stretching demonstrations to prevent text neck syndrome. The community service tools used were pre-tests and post-tests in the form of descriptive questionnaires. Data analysis included descriptive statistics and inferential tests, using the Wilcoxon Signed-Rank Test to compare students’ comprehension levels before and after the education. The results showed an increase in comprehension scores from a pre-test average of 88.24 to 100.00 on the post-test. The Wilcoxon Test results showed a p-value of 0.041, which is less than 0.05 (0.041 < 0.05). These findings indicate that the intervention led to changes in students’ understanding of how to prevent text neck syndrome after the education.